A new crystal form of the NSAID dexketoprofen. Issue 6 (28th May 2019) - Rossi, Patrizia; Paoli, Paola; Ienco, Andrea; Biagi, Diletta; Valleri, Maurizio; Conti, Luca
Abstract : A new crystal form of dexketoprofen, the S ‐enantiomer of ketoprofen, has been characterized in the solid state by SCXRD, DSC and computational methods. A comparison with the already known α form of dexketoprofen is also presented. The thermal behaviour of both polymorphs has been investigated by means of variable‐temperature single‐crystal and microcrystalline powder X‐ray diffraction. Abstract : Dexketoprofen [(2 S )‐2‐(3‐benzoylphenyl)propanoic acid], C16 H14 O3, is the S ‐enantiomer of ketoprofen, a nonsteroidal anti‐inflammatory drug (NSAID) that has analgesic, antipyretic and anti‐inflammatory properties, and finds applications for the short‐term treatment of mild to moderate pain. A new crystalline phase of dexketoprofen is reported. Its solid‐state structure was determined by single‐crystal X‐ray diffraction (SCXRD). The molecular structure of the two independent molecules found in the asymmetric unit of this new phase (DXKP‐β ) were compared to those of the already known crystal form of dexketoprofen (DXKP‐α ) and with the S ‐enantiomer of the racemic compound. The three different conformers of dexketoprofen found in DXKP‐α and DXKP‐β were then investigated by computational methods. The optimized structures are very close to the corresponding starting geometries and do not differ significantly in energy. The crystal packing of DXKP‐β was studied by means of Hirshfeld surface (HS) analysis; interaction energies were also calculated. A comparison with DXKP‐α shows close similarities between the two crystal forms, i.e. in both cases, molecules assemble through the catemer O—H…O synthon of the carboxylic acid stabilized by additional C—H…O contacts and, accordingly, the interaction energies, as well as the contributions to the HS area, are very similar. Finally, the thermal behaviour of the two polymorphs of dexketoprofen was assessed by means of XRD (both from single crystal and microcrystalline powder) and differential scanning calorimetry (DSC); both crystal forms are stable under the experimental conditions adopted (air, 300–350 K for DXKP‐α and 300–340 K DXKP‐β ) and no solid–solid phase transition occurs between the two crystal forms in the investigated temperature range (from 100 K up to ca 350 K).